Three-dimensional mapping of microcircuit correlation structure - Cotton, R. James; Froudarakis, Emmanouil; Storer, Patrick; Saggau, Peter; Tolias, Andreas S. (Frontiers in Neural Circuits, 2013)
Great progress has been made towards understanding the properties of single neurons, yet the principles underlying interactions between neurons remain poorly understood. Given that connectivity in the neocortex is locally dense through both horizontal and vertical con-nections, it is of particular importance to characterize the activity structure of local popula-tions of neurons arranged in three dimensions. However, techniques for simultaneously measuring microcircuit activity are lacking. We developed an in vivo 3D high-speed, ran-dom-access two-photon microscope that is capable of simultaneous 3D motion tracking. This allows imaging from hundreds of neurons at several hundred Hz, while monitoring tissue movement. Given that motion will induce common artifacts across the population, accurate motion tracking is absolutely necessary for studying population activity with ran-dom-access based imaging methods. We demonstrate the potential of this imaging tech-nique by measuring the correlation structure of large populations of nearby neurons in the mouse visual cortex, and find that the microcircuit correlation structure is stimulus-dependent. Three-dimensional random access multiphoton imaging with concurrent mo-tion tracking provides a novel powerful method to characterize the microcircuit activity in vivo.